10.1016/s1541-9800(05)70734-1 (CrossRef Listing of Deleted DOIs, 2000)
Aim To explore nurses' perceptions of how digitalisation influences the delivery of person-centred fundamental care, specifically regarding opportunities, challenges and changes associated with this transformation. Design A qualitative descriptive study. Methods Semi-structured interviews with 25 purposeful sampling of clinical nurses and nurse managers in four hospitals in Italy, where digitalisation was in its initial stages. Data were analysed using content analysis. Results Three main themes illustrate a dynamic tension between digitalisation as a potential enabler of person-centred fundamental care and a potential threat: (a) 'Expanding nurses' capacity towards fundamental care' describes how digital technologies support monitoring, safety and workflow optimisation, potentially freeing time for direct care; (b) 'Being at risk of being taken away from patients' highlights concerns that increased reliance on digitalisation changes nurse-patient relationships and shifts clinical judgement towards technology-driven processes and (c) 'Building nurses' capability to implement digital Fundamentals of Care' explores how digitalisation's implications are shaped by generational experiences in care delivery. Conclusion Digitalisation has the potential to strengthen the integration of physical, psychosocial and relational needs. However, the implementation context, representing the third dimension of the Fundamentals of Care (FoC) framework, appears to moderate both its positive and negative implications for nursing practice. Its influence therefore depends on how digital technologies are embedded within person-centred nursing care. Implications for profession/patient care Digitalisation is reshaping nursing practice, requiring technological innovation and person-centred care to evolve together. Ensuring that digital systems remain aligned with the principles of FoC will be essential for preserving nursing's relational essence while realising the potential of digitalisation. Impact To ensure digitalisation enhances rather than undermines person-centred fundamental care, investment is needed in nursing workforce capacity, education that integrates digital competencies with the FoC framework, and organisational strategies that protect the nurse-patient relationship. Reporting method Consolidated Criteria for Reporting Qualitative Research guidelines. Patient or public contribution Participants were nurses and they were involved in the data collection.